Design and Building Application Alumni Promotion At Institute Business and Informatics Stikom Surabaya - Aditya Putra Nidya; Ayuningtyas Ayuningtyas; Rudi Santoso (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Stikom Career Center (SCC) is a technical implementation unit (UPT) which aims to help or become a mediator between companies / agencies / industry workers, especially those coming from Stikom Surabaya. On the SCC website, alumni still have to find their own job vacancies and the company has not been able to find alumni according to the criteria they need. This process has not been able to help alumni to promote themselves to the world of work. Therefore, the purpose of this research is to build a website-based information system to quick-select suitable candidates or by applicant synchronization in accordance with the needs of vacancies offered by employer. Based on the results of trials that have been conducted in conjunction with SCC Division and PPTI Division Stikom Surabaya then alumni promotional applications can help alumni to promote themselves and help companies who want to find candidates for workers in Stikom Surabaya. with attention to the look and functions used so as to help SCC to bridge alumni Stikom Surabaya in search of work.